2021
DOI: 10.1186/s13046-021-02195-z
|View full text |Cite
|
Sign up to set email alerts
|

ZIP10 is a negative determinant for anti-tumor effect of mannose in thyroid cancer by activating phosphate mannose isomerase

Abstract: Background Mannose, a natural hexose existing in daily food, has been demonstrated to preferentially inhibit the progression of tumors with low expression of phosphate mannose isomerase (PMI). However, its function in thyroid cancer still remains elusive. Methods MTT, colony formation and flow cytometry assays were performed to determine the response of thyroid cancer cells to mannose. Meanwhile, mouse models of subcutaneous xenograft and primary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…For thyroid cancer, one recent study has found that whether the cell line is sensitive to mannose depends mainly on the enzyme activity of PMI (Ma et al, 2021). Structurally, zinc ions (Zn 2+ ) are critical for the binding of the PMI and substrate, so the enzymatic function of PMI depends on Zn 2+ concentration (Bangera et al, 2019).…”
Section: Inhibitory Effect Of Mannose On Various Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For thyroid cancer, one recent study has found that whether the cell line is sensitive to mannose depends mainly on the enzyme activity of PMI (Ma et al, 2021). Structurally, zinc ions (Zn 2+ ) are critical for the binding of the PMI and substrate, so the enzymatic function of PMI depends on Zn 2+ concentration (Bangera et al, 2019).…”
Section: Inhibitory Effect Of Mannose On Various Tumorsmentioning
confidence: 99%
“…ZIP10 is a Zn 2+ transporter expressed during early B cell development that transports Zn 2+ from outside the cell to the cytoplasm, thereby altering the concentration of Zn 2+ within the cell (Miyai et al, 2014). The latest study found that in thyroid cancer cells that are not sensitive to mannose, knocking down ZIP10 can significantly improve their sensitivity to mannose, and M6P accumulation in turn enhances the inhibitory effect of mannose on cellular glycolysis (Ma et al, 2021) (Figure 1). These findings suggest that mannose has potential application value in the treatment of thyroid cancer.…”
Section: Inhibitory Effect Of Mannose On Various Tumorsmentioning
confidence: 99%
“…RNA isolation, cDNA preparation and qRT-PCR were performed as described previously 33 . The mRNA expressions of the indicated genes were normalized to β-actin.…”
Section: Rna Extraction and Quantitative Rt-pcr (Qrt-pcr)mentioning
confidence: 99%
“…Western blot analysis was similarly performed according to the previous protocol 33 . The information of the related antibodies was presented in Supplementary Table S3.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation